2019
DOI: 10.1007/s40092-019-00324-0
|View full text |Cite
|
Sign up to set email alerts
|

Control chart based on residues: Is a good methodology to detect outliers?

Abstract: The purpose of this article is to evaluate the application of forecasting models along with the use of residual control charts to assess production processes whose samples have autocorrelation characteristics. The main objective is to determine the efficiency of control charts for individual observations (CCIO) and exponentially weighted moving average (EWMA) charts when they are applied to residuals of models of AR(1) or MA(1) to detect outlier in autocorrelated processes. Considering autocorrelation strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…If the objective is greater sensitivity, using studentized residuals is better, but if we seek simplicity and interpretation, Pearson residuals can be used. This research showed once again the applicability of residuals of well‐adjusted models to control quality variables, as shown Guarnieri et al 33 …”
Section: Discussionsupporting
confidence: 72%
“…If the objective is greater sensitivity, using studentized residuals is better, but if we seek simplicity and interpretation, Pearson residuals can be used. This research showed once again the applicability of residuals of well‐adjusted models to control quality variables, as shown Guarnieri et al 33 …”
Section: Discussionsupporting
confidence: 72%
“…While programs can be designed with additional features to address high false-positive rates [54] or to prospectively plan for other foreseeable challenges [55], statistical tools are also useful for retrospectively addressing some weaknesses. Among some water quality data, using auto-regressive models for data with equal sampling intervals, e.g., [56], and applying the control chart procedure to the residuals are common approaches. Particular challenges with the water quality datasets available for the OSR, including the lower Muskeg River, include both autocorrelation and unequal intervals between the sampling events.…”
Section: Residual Control Chartsmentioning
confidence: 99%
“…e standard practice in dealing with the autocorrelation problem is tting a time series model to the process data before applying a control chart to the residuals [10][11][12][13][14]. In general, the goal of time series modeling is to obtain accurate forecast [15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely used time series modeling techniques is the Box and Jenkins methodology that works to remove autocorrelation characteristics in process data and thus accepted as standard manufacturing process control practice [1,17]. Autoregressive integrated moving average model (ARIMA) which is based on the above methodology has been employed extensively across various fields, such as in production processes [18,19] and market exchange rates [12,20,21]. e ARIMA model is stable and is doubtlessly used as a benchmark for other time series methodologies.…”
Section: Introductionmentioning
confidence: 99%